The environmental health literacy level was effectively improved of residents in Shaanxi Province, China, 2022 - Feidan Deng; Feidan Deng; Feidan Deng; Xinyue Wen; Xinyue Wen; Guoqiang Dong; Guoqiang Dong; Guoqiang Dong; Xining Wang; Xining Wang; Huifang He; Huifang He; et al. (Frontiers in Public Health)
BackgroundEnvironmental health literacy (EHL) aims to enable individuals to make informed choices to reduce health risks and protect the environment.ObjectivesTo assess the EHL of residents in Shaanxi Province, China in 2022 and analyze the influencing factors.MethodsThis study was a 2022 cross-sectional survey in Shaanxi Province, China, involving 2,237 residents aged 15 to 69. Participants were selected using a multi-stage random sampling method and surveyed through questionnaires in six cities. The weighted rate was calculated using the seventh National Census data, and influential factors were analyzed using multifactor logistic regression.ResultsAccording to the survey, the overall EHL level of Shaanxi residents in 2022 was 15.47%. The first-level classification literacy level of EHL was ranked in descending order: basic skills (21.64%), basic concepts (17.93%), and basic knowledge (14.44%). The EHL level was influenced by age, education level, and occupation. People with higher education and certain occupations were more likely to possess EHL, while older individuals and those with lower education levels, especially in rural areas, were less likely to possess it.ConclusionThe level of EHL among residents in Shaanxi Province in 2022 was higher than in 2020. The findings showed that targeted health education for low EHL groups effectively reduced urban–rural disparities and improved adolescents’ EHL levels.